Empowering Nursing Students: How Video-Based Teaching Enhances Urinary Catheterization Skills – A Randomized Controlled Study - Ayten Kaya; Hanife Durgun (International Neurourology Journal)
Purpose Clinical skills training in nursing aims to equip students with the essential knowledge, skills, and attitudes required to successfully overcome challenges encountered in clinical settings and deliver optimal patient care. This study aimed to evaluate the effectiveness of video-based self-assessment as an educational tool for teaching urinary catheterization—a crucial clinical skill—to nursing students. Methods This study employed a randomized, single-blind, parallel-group controlled design. A total of 61 undergraduate nursing students participated (30 students in the experimental group and 31 in the control group). Students were randomly allocated to either the experimental or control group. The experimental group received conventional teaching methods supplemented by video-assisted education, while the control group received only conventional teaching methods. Pretests and posttests were administered to both groups. Results The experimental group’s mean posttest score regarding urinary system knowledge was higher than that of the control group, but the difference was not statistically significant (P>0.05). However, within the experimental group, the difference between pretest and posttest mean scores on urinary system knowledge was statistically significant. Furthermore, the experimental group’s mean posttest score for urinary catheterization placement skills was significantly higher than that of the control group (P<0.001). Conclusions The video-based self-assessment method effectively enhanced the development of professional skills, such as urinary catheterization, among nursing students.